Negotiating Cultural Identity through Social Media Storytelling: Digital Place Branding of Thematic Villages in Malang, Indonesia - Hiqma Nur Agustina; Yanik Lailinas Sakinah (Journal of Pragmatics Research, 2026)
This study examines how cultural identity is constructed and represented through social media storytelling in the place branding of thematic villages in Malang, Indonesia. The purpose of this research is to explore how digital narratives shape place identity while reflecting and negotiating local cultural values in online spaces. Thematic villages are conceptualized as socially embedded place brands whose meanings are produced through discourse, symbolism, and community participation on social media. The study recognizes that differences in digital literacy, access to resources, and decision-making authority may influence whose cultural voices are represented. It employs a qualitative critical approach using Critical Discourse Analysis (CDA) based on Fairclough’s three-dimensional framework. Data were collected from visual and textual content published on official and community-managed social media accounts of thematic villages in Malang. The analysis focuses on textual features, discursive practices, and broader socio-cultural contexts shaping the production and circulation of digital narratives. The findings show that social media storytelling enhances the visibility and attractiveness of thematic villages by presenting them as creative and culturally distinctive destinations. However, dominant narratives prioritize aesthetic and tourism-oriented representations, often simplifying local cultural practices and values. Cultural elements such as togetherness, social harmony, and local wisdom are highlighted to support branding objectives, while other perspectives receive less attention. Moreover, it reveals a tension between market-driven place branding and the preservation of cultural meanings within local communities. The study contributes to understanding how digital storytelling shape’s cultural identity, place representation, and community-based tourism development.